Epimedium for Osteoporosis Based on Western and Eastern Medicine: An Updated Systematic Review and Meta-Analysis - Shi, Shihua; Wang, Fei; Huang, Yong; Chen, Bonan; Pei, Caixia; Huang, Demei; Wang, Xiaomin; Wang, Yilan; Kou, Shuo; Li, Weihao; Ma, Tianhong; Wu, Yongcan; et al. (Frontiers in Pharmacology, 2022)
Background: The efficacy of conventional pharmacotherapy on osteoporosis was limited accompanying with serious side effects. Epimedium might have the potential to be developed as agents to treat osteoporosis. The present study integrating Western medicine and Eastern medicine was to evaluate the efficacy of Epimedium on osteoporosis. Methods: Eleven electronic databases were searched to identify the randomized controlled trials (RCTs) comparing Epimedium as an adjunctive or alternative versus conventional pharmacotherapy during osteoporosis. Bone mineral density (BMD), effective rate, and Visual Analog Scale (VAS) were measured as primary outcomes. The secondary outcomes were pain relief time, bone metabolic markers, and adverse events. Research quality evaluation was conducted according to the modified Jadad scale. Review Manager 5.4 was utilized to perform analyses, and the data were pooled using a random-effect or fixed-effect model to calculate the weighted mean difference (WMD), standardized mean diﬀerence (SMD), risk ratio (RR), and 95% confidence intervals (CI). Results: Twelve RCTs recruiting 1,017 patients were eligible. Overall, in Epimedium plus conventional pharmacotherapy group, BMD was significantly improved (p = 0.03), effective rate was significantly improved (p = 0.0001), and VAS was significantly decreased (p = 0.01) than those in control group. When compared to conventional pharmacotherapy, Epimedium used alone improved BMD (p = 0.009) and effective rate (p < 0.0001). VAS was lower (p < 0.00001), and the level of alkaline phosphatase (ALP) was significantly decreased (p = 0.01) in patients taking Epimedium alone compared with those given conventional pharmacotherapy. Results of subgroup analyses yielded that the recommended duration of Epimedium as an adjuvant was >3 months (p = 0.03), the recommended duration of Epimedium as an alternative was ≤3 months (p = 0.03), and Epimedium decoction brought more benefits (SMD = 2.33, [1.92, 2.75]) compared with other dosage forms. No significant publication bias was identified based on statistical tests (t = 0.81, p = 0.440). Conclusions: Epimedium may improve BMD and effective rate, and relieve pain as an adjuvant or alternative; Epimedium as an alternative might regulate bone metabolism, especially ALP, with satisfying clinical efficacy during osteoporosis. More rigorous RCTs are warranted to confirm these results.